2008
DOI: 10.1128/aem.01351-08
|View full text |Cite
|
Sign up to set email alerts
|

First Cultivation and Ecological Investigation of a Bacterium Affiliated with the Candidate Phylum OP5 from Hot Springs

Abstract: The phylogenetic group termed OP5 was originally discovered in the Yellowstone National Park hot spring and proposed as an uncultured phylum; the group was afterwards analyzed by applying culture-independent approaches. Recently, a novel thermophilic chemoheterotrophic filamentous bacterium was obtained from a hot spring in Japan that was enriched through various isolation procedures. Phylogenetic analyses of the isolate have revealed that it is closely related to the OP5 phylum that has mainly been constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Prior to developments in molecular techniques, cultivation assays and microscopy were employed to study thermal spring systems (Shivvers and Brock, 1973;Shima and Suzuki, 1993). Although these techniques have advanced our understanding of life in extremes (see Stetter, 1982;Stetter et al, 1981), they prove inadequate when discerning microbial community structure and interaction (Blank et al, 2002;Mori et al, 2008;Kublanov et al, 2009). Since the 1990s, molecular methods such as ribosomal ribonucleic acid (rRNA) gene sequencing via radiolabeling have been used to examine terrestrial hot spring microbial communities (Stahl et al, 1985;Ward et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to developments in molecular techniques, cultivation assays and microscopy were employed to study thermal spring systems (Shivvers and Brock, 1973;Shima and Suzuki, 1993). Although these techniques have advanced our understanding of life in extremes (see Stetter, 1982;Stetter et al, 1981), they prove inadequate when discerning microbial community structure and interaction (Blank et al, 2002;Mori et al, 2008;Kublanov et al, 2009). Since the 1990s, molecular methods such as ribosomal ribonucleic acid (rRNA) gene sequencing via radiolabeling have been used to examine terrestrial hot spring microbial communities (Stahl et al, 1985;Ward et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…After alignment with the ARB program version 5.2 (Ludwig et al, 2004) and the dataset version ssu_jan04.arb, the aligned data were extracted by using the ARB default filter (deinococcus_thermus_rr5_ dec04; 1369 positions) and phylogenetic trees were reconstructed with the neighbour-joining (NJ) method via the CLUSTAL X program version 1.83 (Saitou & Nei, 1987;Thompson et al, 1997) and with the maximum-likelihood (ML) method via the MOLPHY program version 2.3b3 (Adachi & Hasegawa, 1995;Hasegawa et al, 1985;Mori et al, 2008b). The sequence determined indicated that strain AZM34c11 T belonged to the genus Meiothermus in the family Thermaceae.…”
mentioning
confidence: 99%
“…Members of these phyla were found distributed in different extremophilic environments like geothermal and mineral rich soils, [9] deep subsurface [10] aquifers [11,12] and hydrothermal vents [13]. Recently, they were also observed in certain environmental niches, including mesophilic lake water [14] and flooded paddy soils [4].…”
Section: Ecological Occurrence Of Op Phyla and Their Cultivationmentioning
confidence: 99%
“…Analysis of rarefaction curves constructed from the OP11 sequences revealed that species richness in OP11 is not significantly different from that of b-Proteobacteria [17], however, till date they were not represented in culture. Recently, a few strains belonging to the members of OP5 and OP10 have been cultured [9,14,18]. Interestingly, their culturing conditions give us clues to the successful isolation of other members belonging to OP series.…”
Section: Ecological Occurrence Of Op Phyla and Their Cultivationmentioning
confidence: 99%